Characteristics of a 1-year outpatient management of patients after myocardial infarction: data from a Russian multicenter study - A. V. Kontsevaya; A. V. Veretennikova; V. B. Rozanov; M. B. Khudyakov; O. M. Drapkina (Российский кардиологический журнал, 2022)
Aim. To evaluate a 1-year outpatient management of patients after myocardial infarction (MI) aged <75 years according to a Russian multicenter study, as well as to assess compliance with recommendations on the frequency of visiting specialists and the performance of diagnostic examinations.Material and methods. This observational study includes a representative sample of MI patients admitted to 16 clinics in 13 Russian regions. Patients with MI who were alive the next day after hospitalization aged <75 years were included in the study according to a special randomization scheme. When writing this article, the data from questionnaires of 6 and 12 months after hospitalization were analyzed: the number of visits to doctors of various specialties, hospitalizations, the number of diagnostic procedures performed (electrocardiography (ECG), echocardiography and surgical interventions (percutaneous coronary intervention, coronary artery bypass grafting (CABG)). The study included a cohort of 723 patients who participated in the survey both 6 and 12 months after hospitalization (67% — patients discharged from the hospital), of which 562 (77,7%) were men and 161 (22,3%) — women. Statistical processing was performed using IBM SPSS Statistics v.25 software for Windows.Results. In the first 6 months after MI, 218 (38,8%) men and 62 (38,5%) women visited the cardiologist the recommended number of times. However, 151 (20,9%) people were not monitored by a cardiologist in the first six months. There was a significant increase in the number of people not observed during the second 6 months up to 209 (28,9%) people (p<0,01). Of the 689 interviewed patients, 210 (30,5%) people visited the therapist the recommended number of times in the first six months, while in the second 6 months — 402 (58,4%) patients. It is also reasonable to single out patients who were not monitored by either a cardiologist or a general practitioner into a separate group. In the first 6 months, the total number of unobserved patients was 68 (7,5%), while in the second six months this number increased to 189 (25,9%). The recommended number of ECGs (4 or more times) was performed in 316 (40,4%) patients, while ECG was not performed in 35 (4,5%) patients. Echocardiography 2 or more times was performed in 194 (25,4%) patients. The procedure was not performed in 167 (21,9%) patients. During the first 6 months, 170 (22%) people were hospitalized, while 156 (20,2%) — during the second half of the year. Angioplasty during the first 12 months after discharge from the hospital was performed in 183 (23,1%) patients, CABG — in 41 (5,2%) patients without age and sex differences.Conclusion. Outpatient management of patients aged <75 years 12 months after MI characterized by low compliance with recommendations on the number of cardiologist consultations and diagnostic procedures, which may adversely affect adherence to the recommended drug treatment and lead to a worse prognosis.